What are markets? Selected market theories under genuine uncertainty in comparison - Ute Schmiel; Hendrik Sander (Journal of Evolutionary Economics, 2021)
Since market economies are the dominant form of regulating economic action all over the world, the question arises how markets are conceived theoretically. Answering this is relevant because we need to know how existing and hypothetical markets work in general, what they “can do”, and how one can improve the market order. There are three different market approaches that consider genuine uncertainty. According to the new institutional economics approach, markets are institutions that increase boundedly rational actors' utility. The markets-as-institutional-arrangements approach denies that markets maximize or minimize market outcomes and argues that they enable harmony between individual and common interests. According to the political-cultural approach, markets are political arenas with conflicts between the relevant actors. Deciding reasonably for a theory requires answering whether one theory is more adequate than another. Since literature has not answered this so far, the present paper deals with this issue from a critical-rationalist perspective. It finds that the institutional economics approach is not adequate because its assumptions contradict reality and each other. In contrast, the markets-as-institutional-arrangements approach and the political-cultural approach fulfill critical-rationalist requirements. Therefore, the paper compares them and finds that there are reasons to prefer the political-cultural approach and to interpret the markets-as-institutional-arrangements approach as its special case. Referring to the political-cultural approach has different consequences for analyzing and improving the market order. Taking a political-cultural view implies, e.g., not only focusing on desirable social values and market rules but also on the relevance of interpretative frameworks and power.
Keywords: A11; B41; B52; D49; D72; 330; Genuine uncertainty; Markets-as-institutional-arrangements approach; Market theories; New institutional economics; Political-cultural approach